Acute kidney injury after primary total hip arthroplasty: a risk multiplier for complication, mortality, and healthcare utilization - Jasvinder A. Singh; John D. Cleveland (Arthritis Research & Therapy, 2020)
Abstract Objective To assess whether acute kidney injury (AKI) is associated with more complications and higher healthcare utilization in people undergoing primary total hip arthroplasty (THA). Methods Using a retrospective cohort study design, we performed multivariable-adjusted logistic regression of the 1998–2014 US National Inpatient Sample data to assess the association of AKI with complications (infection, transfusion, revision, and mortality) and healthcare utilization (total hospital charges, discharge to a rehabilitation facility, length of hospital stay) post-THA. We calculated the odds ratio (OR) and 95% confidence intervals (CI). Results Adjusted for age, gender, race, income, underlying diagnosis, medical comorbidity, and the insurance payer, AKI in people who underwent primary THA was associated with significantly higher OR (95% CI) of (1) implant infection, 2.34 (95% CI, 1.87, 2.93); (2) transfusion, 2.46 (95% CI, 2.37, 2.56); (3) revision, 2.54 (95% CI, 2.16, 2.98); (4) death, 8.52 (95% CI, 7.47, 9.73); (5) total hospital charges above the median, 2.29 (95% CI, 1.99, 2.65); (6) discharge to a rehabilitation facility, 2.11 (95% CI, 2.02, 2.20); and (7) hospital stay > 3 days, 4.34 (95% CI, 4.16, 4.53). Conclusion Quality improvement initiatives with optimization of the peri-operative care to reduce AKI and subsequently AKI-associated complications and healthcare utilization are needed. Mechanisms of AKI-associated post-THA complications need further examination.